Spatiotemporal Neural Dynamics of Word Understanding in 12- to 18-Month-Old-Infants - Travis, Katherine E. (Oxford University Press, 2011)
Learning words is central in human development. However, lacking clear evidence for how or where language is processed in the developing brain, it is unknown whether these processes are similar in infants and adults. Here, we use magnetoencephalography in combination with high-resolution structural magnetic resonance imaging to noninvasively estimate the spatiotemporal distribution of word-selective brain activity in 12- to 18-month-old infants. Infants watched pictures of common objects and listened to words that they understood. A subset of these infants also listened to familiar words compared with sensory control sounds. In both experiments, words evoked a characteristic event-related brain response peaking ∼400 ms after word onset, which localized to left frontotemporal cortices. In adults, this activity, termed the N400m, is associated with lexico-semantic encoding. Like adults, we find that the amplitude of the infant N400m is also modulated by semantic priming, being reduced to words preceded by a semantically related picture. These findings suggest that similar left frontotemporal areas are used for encoding lexico-semantic information throughout the life span, from the earliest stages of word learning. Furthermore, this ontogenetic consistency implies that the neurophysiological processes underlying the N400m may be important both for understanding already known words and for learning new words.